The Effect of Xylitol as a Natural Admixture on the Properties of Alkali-Activated Slag/Fly Ash-Based Materials - Jie Song; Haowei Hu; Weitong Yu (Buildings)
This study introduces xylitol, a natural compound, as a multifunctional additive to enhance the performance of alkali-activated slag/fly ash materials (AASFMs). A systematic investigation was conducted to elucidate xylitol’s mechanism in modifying AASFM properties, including fresh behavior, hydration kinetics, compressive strength, and autogenous shrinkage. The experimental findings demonstrated that xylitol significantly delayed early-age hydration while promoting more extensive hydration at later stages. Specifically, the initial and final setting times of AASFM pastes were extended by 640% and 370%, respectively, and paste flowability increased by 30%. At a 0.2% dosage, xylitol markedly reduced porosity and refined the microstructure of AASFMs, leading to improved mechanical properties. The 3-day and 28-day compressive strengths were enhanced by 39.8% and 39.7%, respectively, while autogenous shrinkage was suppressed by 61.4%. These results demonstrate the multifunctional potential of xylitol in AASFMs, serving as an effective retarder, plasticizer, strength enhancer, and shrinkage reducer. Notably, the refined pore structure induced by xylitol may also mitigate the risks of the alkali–silica reaction, though further durability validation is warranted.